THE POLITICAL SITUATION IN AFGHANISTAN BEFORE AMIR AMANULLAH KHAN (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article covers the political processes that occurred before the rise to power of Amir Amanullah Khan, who implemented major reforms in the history of Afghanistan. The article is also enriched with the scientific work of scholars studying the history of Afghanistan, ensuring that the information presented has a scientific basis.